PELATIHAN PEMBELAJARAN DARING DI SD NEGERI 1 BANTAS SELAMA PANDEMI COVID-19 - I Wayan Mawa; I Made Suparta; Ni Wayan Sadri; Ida Bagus Rai Putra; I Gede Bagus Wisnu Bayu Temaja (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2025)
The purpose of this community service article is to report on online learning training for teachers at SD Negeri 2 Bantas, Bali during the Covid-19 pandemic. This training was held on August 24, 2020. The implementation of this training applied interview, observation, presentation, and lecture methods. Various activities were carried out in this activity, especially related to the introduction of online-based learning devices for teachers. The results of this activity were that teachers were able to use various online-based learning suggestions. The problems or issues faced in the online learning process at SD Negeri 2 Bantas were problems related to teacher competence, problems with differences in students’ understanding levels, problems with parents who did not have Android, lack of cooperation between parents and students, and limited facilities and infrastructure. The solution taken to solve the problem of online learning at SD Negeri 2 Bantas is that teachers can attend seminars or training on information technology and peer learning, provide guidance or assistance to children in groups or individually, provide counseling and hold meetings with guardians regarding the importance of using Android in the learning process, provide an understanding of the importance of parental cooperation in supervising their children learning from home, and hold parental cooperation to photocopy textbooks so that students can continue to learn. Through this training, it is hoped that it will be able to answer the problems faced by teachers.